2008
DOI: 10.1371/journal.pbio.0060215
|View full text |Cite
|
Sign up to set email alerts
|

Texture Coding in the Rat Whisker System: Slip-Stick Versus Differential Resonance

Abstract: Rats discriminate surface textures using their whiskers (vibrissae), but how whiskers extract texture information, and how this information is encoded by the brain, are not known. In the resonance model, whisker motion across different textures excites mechanical resonance in distinct subsets of whiskers, due to variation across whiskers in resonance frequency, which varies with whisker length. Texture information is therefore encoded by the spatial pattern of activated whiskers. In the competing kinetic signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
269
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(295 citation statements)
references
References 37 publications
20
269
2
Order By: Relevance
“…Thalamic Adaptation Is Reduced by L6 Activation. Behaviorally relevant inputs for mice and rats are sequences of whisker stimuli that occur when a mouse rhythmically moves its whiskers during exploration and when the whiskers are swept along objects with uneven surfaces (32). As in other sensory thalamo-cortical systems, VPM neurons exhibit characteristic rapid adaptation to sensory inputs (6,33,34).…”
Section: Resultsmentioning
confidence: 99%
“…Thalamic Adaptation Is Reduced by L6 Activation. Behaviorally relevant inputs for mice and rats are sequences of whisker stimuli that occur when a mouse rhythmically moves its whiskers during exploration and when the whiskers are swept along objects with uneven surfaces (32). As in other sensory thalamo-cortical systems, VPM neurons exhibit characteristic rapid adaptation to sensory inputs (6,33,34).…”
Section: Resultsmentioning
confidence: 99%
“…Mice use their whiskers for vibrotactile perception mediated by high frequency changes in whisker position (Wolfe et al 2008;Jadhav et al 2009;Mayrhofer et al 2015). Recently, our group characterized the neuronal population response to increasing frequencies of whisker deflection and found that while many neurons respond weakly to stimulation, a subset of highly-responding neurons (~3%) reliably discriminate different stimuli (Mayrhofer et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In order to study the local astrocyte response to somatosensory activation, we used two different stimulation paradigms: electrical hindpaw stimulation (400 µA at 4 Hz for 5 s, Movie 1) and single whisker deflection (1 s duration) at different frequencies known to mimic "stick-slip" events from whisking on textured surfaces (Movie 2; (Wolfe et al 2008;Jadhav et al 2009;Mayrhofer et al 2015)). …”
Section: Astrocytes Respond To Sensory Stimulationmentioning
confidence: 99%
“…2B), the sensory system may record whisking motion equally well, no matter whether it is periodic or irregular 24). On the other hand, during object contact, whisker motion can be characterized as an irregular vibration containing frequencies up to a few hundred Hz (25)(26)(27)(28)(29)(30)(31)(32). The "noisiness" of such kinetic profiles would evoke a particularly robust and temporally precise cortical response.…”
Section: Discussionmentioning
confidence: 99%